(untitled) (Research, Society and Development, 2021)
Violence against women is a public health problem, its magnitude is largely invisible. The prevention and confrontation of violence against women, especially physical violence, harms their mental health. This type of violence has been very common in the family environment, especially by intimate partners. Therefore, the study aims to analyze the scientific production existing in the Brazilian literature on physical violence against women and the damage caused by their partners to their mental health. This is an integrative literature review on the aforementioned topic carried out in the Scientific Electronic Library Online (SCIELO), Latin American Literature in Health Sciences (LILACS) and Brazilian Nursing Databases (BDENF) databases in the period from June to July 2019, where 16 articles were found. It was observed that violence has been increasingly aggravated among women. Where we can initially reference the physical aggressions that are more severe. The fear and imprisonment that women live due to aggressions in their home environment lead to serious consequences for mental health, depression and post-traumatic stress, which were considered the most frequent found in the articles. Therefore, it is necessary that health professionals can acquire a careful look, seek, through qualified listening, the trust and the necessary bond to carry out effective actions and forms of prevention of physical violence to deal with women who have been or are victimized.